Wiley international trends in financial reporting under IFRS : including comparisons with US GAAP, China GAAP, and India accounting standards - Mirza, Abbas Ali.; Nandakumar, Ankarath (Hoboken, N.J. : Wiley, 2013)
International Financial Reporting Standards (IFRS) are gaining importance daily. With more than 100 countries having adopted these standards and the finance ministers of G20 nations calling for global convergence of accounting standards, a substantial need has emerged to learn and understand how to apply them in practice. Filled with real-world examples and case studies, this handy resource: Explores the practical application of international accounting standards to financial statements; Offers copious examples of footnote disclosures and financial statement formats from many of the world's IFRS-compliant reporting entities, including BAE Systems, Lufthansa Group, Aviva, BP, Samsung Electronics, Addeco, and more; Includes IFRS compliance checklists. With a topical arrangement that follows the blueprint of all international accounting standards products, Wiley International Trends in Financial Reporting under IFRS deftly bridges the gap in IFRS literature with a rare look at actual IFRS financial statement disclosures from internationally operational companies. Get the practical insights you need into IFRS application with the easy-to-navigate guidance found in Wiley International Trends in Financial Reporting under IFRS. --Book Jacket.
Introduction to International financial reporting standards (IFRS) -- IASB framework for the preparation and presentation of financial statements -- Presentation of financial statements (IAS 1) -- Statement of cash flows (IAS 7).
Includes index.
Keywords: Financial statements; Corporation reports -- Periodicals; Accounting -- Standards; International business enterprises -- Accounting